The design activity of the teacher in the context of the implementation of the morphological matrix of lesson’s innovative elements - Shtefan, L. (Problems of Engineer-Pedagogical Education, 2018)
A modern innovative paradigm in education greatly is realized with project approaches introduction in the pedagogical process which allowed considering the basic links of pedagogical process integrally and system. There was in the highlight article determination the planning of the modern lesson in professional-technical educational establishments. To the lead through of this work became methodological subsoil cognitive, active, competitive, personality-oriented, differentiated, cultural approaches and conception of autopoetic systems. Among basic methods which are used in research, there was a method of morphological analysis and pedagogical technique ways, which is used in a basis of lesson designer. As a result of this scientific research became an adaptation of algorithm with morphological analysis method usage for the terms of lesson planning. On that ground a morphological matrix with its innovative elements was developed. Its application will allow to transfer a lesson planning to the creative plane, where a lesson will be examined as a synergistically system which all of time is in the dynamic state.